Nepenthes of Kerangas Forest of Tuing towards Insect - Hidayati, Nur Annis (Media Konservasi, 2018)
Kerangas forest, is a distinct vegetation around the tropics. It has a highly acidic soils and low nutrition contents. This condition lead to a uniqueness of its community member, as shown by Nepenthes spp. Nepenthes spp. are carnivorous plants which use insect as their nitrogen source. This research aimed to predict the role of Nepenthes spp. of kerangas forest towards insect through insect composition in the pitchers of Nepenthes spp.. This was a descriptive qualitative research. Research was conducted during May, 2018 in kerangas forest of Tuing, Bangka. Eight 10m x 10m plots were placed by purposive sampling. Results showed that there were 266 insects found in 23 Nepenthes spp. pitchers, identified as Ordo Coleoptera, Diptera, Hymenoptera, and Orthoptera. There was no difference between composition of aerial and terrestrial pitcher. Insects found grouped as beneficial insect, pollinator, and others. Alive Culicidae larvae was the most abundant insect found within its’ pitchers. It showed the Nepenthes spp. role in kerangas forest as a potential mini-habitat for aquatic larvae. Nevertheless, further study is needed to prove regarding temporal variation in liquid composition in Nepenthes spp. pitcher. Keywords: insect, kerangas, Nepenthes spp., role